Deutscher Wortschatz im 17. Jahrhundert methodologische Studien zu Korpustheorie, Lexikologie und Lexikographie von historischem Wortschatz - Schulz, Matthias 1969- (Reihe Germanistische Linguistik, 2007)
Matthias Schulz examines corpus theory, lexicology and lexicography with reference to historical vocabulary and its lexical structures. The author first analyses how historical lexes and lexical structures are collected and examined and then selects 85 texts from everyday life in the 17th century. These form the basis for his own analyses of individual areas of lexis. His case studies reveal lexical structures in 17th century vocabulary. The corpus used in his study is online available: http://www.degruyter.com/view/product/36681